Oblicza migracji – „gorący” temat na zajęciach języka polskiego jako obcego .......... 109 - Szałasta-Rogowska, Bożena (Kultura i literatura w glottodydaktyce polonistycznej wobec wymagań rzeczywistości, 2025)
FACES OF MIGRATION – A HOT TOPIC DURING POLISH AS A FOREIGN LANGUAGE CLASSES The article concerns the use of Polish as a foreign language in classes on topics related to the phenomenon of migration. This is a very extensive and important topic, which often appears as a leitmotif in Polish poetry of the 20th and 21st centuries. A brief historical and literary characterization of emigration and migration is the basis for the second, practical part of the text. The author of the article proposes introducing poems by Bogdan Czaykowski, Joanna Ewa Jarzymowska, Tomasz Mielcarek and Roman Chojnacki into the language classes. Each proposal for language classes based on poetic texts is preceded by an analysis and interpretation of poetry in the article in order to become an effective tool in the hands of glottodidactics.